Delorme's Procedure for Complete Rectal Prolapse: A Study of Recurrence Patterns in the Long Term. (10th December 2015) - Placer, Carlos; Enriquez-Navascués, Jose M.; Timoteo, Ander; Elorza, Garazi; Borda, Nerea; Gallego, Lander; Saralegui, Yolanda
Abstract : Introduction . The objective of this study was to determine the recurrence rate and associated risk factors of full-thickness rectal prolapse in the long term after Delorme's procedure. Patients and Methods . The study involved adult patients with rectal prolapse treated with Delorme's surgery between 2000 and 2012 and followed up prospectively in an outpatient unit. We assessed epidemiological data, Wexner constipation and incontinence score, recurrence patterns, and risk factors. Data were analyzed by univariate and multivariate studies and follow-up was performed according to Kaplan-Meier technique. The primary outcome was recurrence. Results . A total of 42 patients, where 71.4% (n = 30 ) were women, with a median age of 76 years (IQR 66 to 86), underwent Delorme's surgery. The median follow-up was 85 months (IQR 28 to 132). There was no mortality, and morbidity was 9.5%. Recurrence occurred in five patients (12%) within 14 months after surgery. Actuarial recurrence at five years was 9.9%. According to the univariate analysis, constipation and concomitant pelvic floor repair were the only factors found to be associated with recurrence. Multivariate analysis showed no statistically significant differences among variables studied. Kaplan-Meier estimate revealed that constipation was associated with a higher risk of recurrence (log-rank test, p = 0.006 ). Conclusions . Delorme's procedure is a safe technique with an actuarial recurrence at five years of 9.9%. The outcomes obtained in this study support the performance of concomitant postanal repair and levatorplasty to reduce recurrences. Also, severe constipation is associated with a higher recurrence rate.